A national survey of adult safeguarding in NHS mental health services in England and Wales. (2013) - Fanneran, Tina Brigid; Kingston, Paul; Bradley, Eleanor
Abstract : Background: Following the introduction of the No Secrets (Department of Helath, (2000). No Secrets: Guidance on Developing and Implementing Multi-agency Policies and Procedures to Protect Vulnerable Adults from Abuse . London: HMSO) guidance, the implementation and development of adult safeguarding practices and procedures across national services has become an ongoing endeavour. Despite existing research highlighting practice improvements in many services, NHS mental health services are persistently criticised for their lack of engagement with the national adult safeguarding agenda (Department of Health (2009) . Safeguarding Adults: Report on the Consultation on the Review of 'No Secrets' . London: HMSO). Aim: To investigate the organisational structure, implementation and development of adult safeguarding in NHS mental health services. Method: A cross-sectional survey was distributed on-line to 79 (72 NHS Mental Health Trusts in England and seven Health Boards in Wales) NHS mental health services. Results: Thirty-three completed surveys were returned, yielding a response rate of 41%. The results highlight adequate arrangements for adult safeguarding in many services; however, it appears implementation is in its initial stages. Responses suggest that staff attitudes and uptake of training are the greatest barrier to practice; however, barriers are also indicated at a strategic and operational level. Conclusion: The importance of adult safeguarding must be recognised at all levels and there is an immediate need for improvement to staff training and engagement to ensure future effective practice in this area.